Evaluasi Kurikulum Terintegrasi Antara Pondok Pesantren Dan Madrasah - Leli Sobali (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2023)
This study examines the evaluation of the integration curriculum at the maadrasa and pesantren. This study aims to discuss the results of the integrated curriculum concept, the implementation of the integrated curriculum and the results of the evaluation of this integration curriculum. The research method is a qualitative descriptive approach through interviews, observations, and documentation. The results of this study indicate that the concept of an integrated curriculum madrasa and pesantren uses an integrated system/integration between the modern system and the salafi system. Then in implementing this integration curriculum has 3 forms: first, the Koran (religious education) which is learning to read Arabic texts, especially the Qur'an and classical books (the yellow book). Second, experience and moral education. Life experiences taught in Islamic boarding schools and appreciation of moral values, including simplicity, Islamic brotherhood, sincerity and human values. Third, madrasa or general education. And lastly, the evaluation of the integration curriculum is divided into 4 components, namely the context component (curriculum foundation, community needs and eligibility of the organizing institution), input component (student recruitment, ustadz condition and assessment of learning facilities), process component (learning implementation of learning and additional hours outside the specified hours) and the last component of the product (PAS and PAT results, achievements and community responses).